Third Sector and Governance: : An Overview - Haque, Md. Moynul (The Jahangirnagar Review, 2025)
In many third world countries, a new mode of governance has emerged that involves multiple stake holders in supporting service delivery in places where central authorities (government) lack the ability to provide public goods. In such areas of limited statehood, state has embraced the non-hierarchical mode of coordination of Third Sector Organizations, for example charity, in the fields of welfare provision, education, environment and community development. As such, third sectors have increasingly gained importance as complementary service provider, side by side the state. Therefore, the actor’s constellation consisting of state and non-state actors in public governance offers an important subject of investigation. While academic literatures have addressed the role of non-state actor in the promotion of good governance, it is however, interesting that scholars have paid little attention to the role of third sector as effective component to governance contribution. This paper attempts to fill this knowledge gap. The objective of this paper is to study the role of third sector in service delivery provisions. In so doing, it uses thematic literature review method. The data source includes published books and articles. The analysis suggests that third sectors play a pivotal role in the social welfare provision alongside formal government structures in many parts of the world. The result also underscores that charity organizations–which is neither private nor public but the various forms of cooperative, mutualistic and associative organizations–essentially emerged as major stakeholder in the collaborative governance framework to fill the service gaps left by the state. The paper concludes by arguing that in the changing mode of governance, it is important to know how social welfare provision is organized and who is involved in this complex service delivery landscape. The study of third sector agencies, for example role of charities, is one important avenue for better understanding this issue.